Influence of Chrysanthemum morifolium-maize intercropping pattern on yield, quality, soil condition, and rhizosphere soil microbial communities of C. morifolium - Liao, Zhiyuan; Chen, Qiaohuan; Li, Jinxin; Wei, Lu; Wu, Jialiang; Wang, Xiao; Liu, Qi; Miao, Yuhuan; Liu, Dahui (Frontiers in Plant Science, 2024)
Chrysanthemum morifolium Ramat. is a perennial herb in the Compositae family, often employed in traditional Chinese medicine due to its medicinal value. The planting of C. morifolium faces the challenges of continuous cropping, and intercropping is able to somewhat overcome the obstacles of continuous cropping. In our study, we designed two different C. morifolium-maize intercropping patterns, including C. morifolium-maize narrow-wide row planting (IS) and C. morifolium-maize middle row planting (IM). Compared with monoculture, the agronomic traits, yield, active ingredients, soil physicochemical properties, soil enzyme activities, and rhizosphere soil microbial communities of C. morifolium and maize were measured under the two C. morifoliummaize intercropping patterns. The findings indicated that (1) Intercropping elevated the agronomic traits, yield, and active ingredients of C. morifolium, especially in C. morifolium-maize narrow-wide row planting pattern, which indicating that interspecific distance played an important role in intercropping system; (2) Intercropping enhanced soil physicochemical properties and enzyme activities of C. morifolium and maize; (3) Intercropping altered rhizosphere soil microbial communities of C. morifolium and maize, making microbial interrelationships more complex. (4) Intercropping could recruit a large number of beneficial microorganisms enrich in the soil, including Bacillus, Sphingomonas, Burkholderia-Caballeronia-Paraburkholderia, Chaetomium, and Ceratorhiza, which may increased the content of AN, NN, AvK, ExCa, AvCu, AvZn and other nutrients in soil and promoted the growth and quality of C. morifolium. In summary, intercropping with maize could promote the accumulation of beneficial microorganisms in the soil, thus improving the overall growing environment, and finally realizing the growth and improvement of C. morifolium.